Ecology and Conservation of Parrots in Their Native and Non-Native Ranges - Tella, José; Blanco, Guillermo; Carrete, Martina (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on parrots, which are among the most fascinating, attractive, and threatened birds, combining and synthesizing recent research on the biology, ecology, and conservation of both native and non-native parrot populations across the world.